Anterior Chamber Dislocation of Dexamethasone Implant in the Presence of Carlevale Sutureless Scleral Fixation Intraocular Lens - Panagiotis Stavrakas; Panos Gartaganis; Styliani Totou; Evangelia Chalkiadaki; Evangelos Manousakis; Efthymios Karmiris (Case Reports in Ophthalmology, 2023)
Dexamethasone intravitreal implant (Ozurdex®; Allergan, Inc., CA, USA) has been proved to be effective in a variety of clinical settings including cases of pseudophakic cystoid macular edema. Uncommonly, this implant can migrate from the vitreous cavity and into the anterior chamber, especially in vitrectomized eyes with lens capsule defects. We report herein a rare case of anterior chamber migration and illustrate the passageway of the dexamethasone intravitreal implant through a new type of scleral fixated lens, the Carlevale IOL (Soleko-Italy). A 78-year-old woman was left aphakic following a complicated right eye hypermature cataract surgery with posterior capsule rupture and zonular dehiscence. Shortly thereafter, she underwent a planned combined pars plana vitrectomy with the placement of a Carlevale sutureless scleral fixated intraocular lens for the treatment of her aphakia. Due to a subsequent persistent cystoid macular edema that was unresponsive to topical treatment and sub-tenon corticosteroids, an intravitreal dexamethasone implant was injected. Eleven days after implantation, the patient presented with a floating implant in the anterior chamber and corneal edema. Following an immediate surgical removal, corneal edema resolved and visual acuity improved. One year later, results remain stable without macular edema recurrence. Anterior chamber migration of the Ozurdex implant is a potential complication in vitrectomized eyes, even when new types which are larger and specially designed for scleral fixation intraocular lenses are utilized. Corneal complications can be reversible following an immediate removal of the implant.